TANGGUNG GUGAT DALAM TRANSAKSI MELALUI INTERNET BANKING - Kuwido Prahoro; Trisadini Prasastinah Usanti (Fakultas Hukum Universitas Narotama, 2019)
Economic development in Indonesia is inseparable from the strategic role held by banking institutions. The important position of the bank in supporting the economic activities of the community creates a business orientation for the bank in conducting various transactions. In developing its business, the bank utilizes technological advances to improve systems and services for customers. One form of banking services that utilizes technology is the creation of internet banking services. Internet banking services make it easy for customers to conduct banking transactions anywhere and anytime. Efficiency and effectiveness are the advantages of internet banking, so that it becomes an attraction for customers to use internet banking services. But on the other hand, internet banking services are also prone to be misused by parties who are not responsible for taking advantage through cybercrime. In this journal, the author focuses on the forms of misuse of internet banking services and accountability if losses arise due to the use of internet banking services. Hopefully this journal can be a useful reading and add insight to the reader